Process of hop particle precipitation in combined wort brew machine - Chepeliuk, Oleksandr; Udodov, Sergiy; Chepeliuk, Olena (My University, 2024)
A mathematical model of separating solid particles of crushed hops from wort has been developed to improve the combined wort brew machine. A formula for determining the radius of the sediment formation area, which depends on the characteristics of the medium, the operating modes of the apparatus, and the functions characterising the velocity distribution in the boundary layer, is proposed. A dependence for calculating the deposition rate at which moving particles settle to the bottom of the combined wort brew machine is obtained. Based on the obtained results, recommendations on the design and operating parameters of the apparatus are given.

Розроблена математична модель процесу відокремлення від сусла твердих частинок подрібненого хмелю з метою удосконалення комбінованого сусловарильного апарату. Запропоновано формулу визначення радіусу області утворення осаду, який залежить від характеристик середовища, режимів роботи апарата та функцій, що характеризують розподіл швидкостей у пограничному шарі. Отримано залежність для розрахунку швидкості відкладання, при якій часточки, що рухаються, осідають на дно комбінованого сусловарильного апарату. На основі отриманих результатів дано рекомендації по конструкційних і режимних параметрах апарату.
Keywords: wort brew machine; particles; sedimentation; stirrer; speed; сусловарильний апарат; часточки; осідання; мішалка; швидкість; кафедра машин і апаратів харчових та фармацевтичних виробництв